THROUGH INJURY IN THE ELDERLY IN NAM DINH CITY YEAR 2021 (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the current situation of injuries caused by falls in the elderly in the city Nam Dinh in 2021. Subjects and research methods: Cross-sectional description of the consequences of injury from falls in the elderly, from January 2021 to December 2021, in 4 wards and communes: Nam Van, Nam Phong, My Xa, Loc Hoa - Nam Dinh City. Results: Injuries due to falls in the elderly encountered 130/400 subjects, accounting for 32.5%, the most injured age was 66, the lowest age was 60, the highest 99, the average age was 76.48, age group ≥80 accounted for 62.3%, female 66.2%, retired and housewife 57.7%. Elderly people who fell by themselves suffered multiple injuries 31.7%, and 40.0% due to other people's injuries. Time of falls in the evening 77.7% and while moving 84.4%. Injuries caused by first aid relatives accounted for 77.7%, medical staff gave first aid 0.8%. Injuries treated at provincial hospitals 30.0%, at health stations 14.6%, self-medicated 23.8%. Treatment costs ≤1 million accounted for 40.8%, full recovery in the first week 93.4%, self-help after falling in the first week accounted for 73.6%. Conclusion: Injuries from falls affect the quality of life of the elderly in the community.
Keywords: Situation of injuries, fall injuries, injuries in the elderly.